Finance & Economics Readings Selected Papers from Asia-Pacific Conference on Economics & Finance, 2017 (Springer Singapore, 2018)
This book is a compilation of the best papers presented at the 2017 installment of the Asia-Pacific Conference on Economics & Finance (APEF), which is held annually in Singapore. With a great number of submissions, it presents the latest research findings in economics and finance and discusses relevant issues in today's world. The book is a useful resource for readers who want access to economics, finance and business research focusing on the Asia-Pacific region.